Theory of Film Practice - Burch, Noël, 1932- (Book collections on Project MUSE., 1981)
This classic in film theory, presents a systematic study of the techniques of the film medium and of their potential uses for creating formal structures in individual films such as Dovzhenko's Earth, Antonioni's La Notte, Bresson's Au Hasard Balthazar, Renoir's Nana, and Godard's Pierrot le Fou. Originally published in 1981. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.